Maculopapular drug eruption with histopathological features of psoriasiform drug eruption in a patient with psoriasis vulgaris: a case report - Kevin Jonathan Djuanda; Nyoman Suryawati; I. G. A. A. Elis Indira; Herman Saputra (Published by Universitas Gadjah Mada, 2025)
Maculopapular drug eruption in patient with psoriasis are rarely reported and require close monitoring during oral corticosteroid therapy due to the potential risk of flare following dose reduction or discontinuation. A 47-yo male with a history of psoriasis vulgaris on cyclosporine therapy developed erythematous patches with scaling following the administration of amoxicillin, mefenamic acid, and antitetanus injection after a nail puncture injury. Vital signs were within normal limits. Dermatological examination revealed multiple well-demarcated erythematous macules, patches, and papules with geographic patterns measuring 0.6×0.9 cm to 2.5×4 cm, some confluent, accompanied by white scales and desquamation. Histopathological findings were consistent with psoriasiform drug eruption. The Naranjo score for amoxicillin was 4, showed a possible correlation. A diagnosis of maculopapular drug eruption suspected to be induced by amoxicillin was established. Clinical improvement observed following the administration of oral corticosteroids, cyclosporine, antihistamines, and emollients. The diagnosis of maculopapular drug eruption requires correlation of rash onset and drug initiation as well as monitoring of symptom resolution after drug discontinuation the suspected drug. Histopathological examination may support the diagnosis, with the presence of eosinophils serving as an indicator of drug-induced etiology. Management of maculopapular drug eruption in patients with psoriasis includes withdrawal of the suspected causative agent, symptomatic therapy, systemic corticosteroids, and immunosuppressive treatment as indicated.